The Impact of Digital Banking Technology Development on MSME Growth in Sidoarjo Regency - Rezi Panji Pamungkas; Nur Laely; Angga Rizka Lidiawan (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to determine the effect of the development of digital banking technology on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo Regency. Digital services such as mobile banking, QRIS, and online loans are considered capable of supporting MSMEs in running business operations more efficiently. This study applies a quantitative approach with a simple linear regression method. Data were collected through questionnaires distributed to 100 MSME players who have utilized digital banking services and were analyzed using SPSS software version 25. The results indicate that digital banking technology has a positive but insignificant effect on MSME development, with a significance value of 0.387 (> 0.05) and an R² of 0.008. This implies that the adoption of banking technology has not yet had a substantial impact on the growth of MSMEs in Sidoarjo.